Assessment of Bacterial Community Structure in Saline Sediment Microcosms Exposed for the First Time to the Ionic Liquid 1-Ethyl-3-Methylimidazolium Chloride - Pal, Srikanta; Sar, Abhijit; Biswas, Raju; Misra, Arijit; Banerjee, Sohini; Dam, Bomba (Water, air, and soil pollution, 2021)
Ionic liquids, such as 1-ethyl-3-methylimidazolium chloride ([Emim]Cl), have immense applicability as solvents in different industrial settings including lignocellulosic biofuel production. However, these solvents are toxic to most organisms. Moderate halophiles are an established microbial group that can tolerate [Emim]Cl by employing their general salt-tolerant mechanisms. Anticipating future exposure of [Emim]Cl to natural environments, the present study was designed to evaluate bacterial community structure in slightly saline (20 g L −1 or 2%) sediments of Sambhar Salt Lake, Rajasthan, India, after microcosm enrichment with [Emim]Cl. The sediment used does not have any native [Emim]Cl (100 mM)–tolerant bacteria. However, after a two-step enrichment of 25 days each with 0.5 M and 1.0 M [Emim]Cl, the tolerant colonies increased to 54.9% and 93.0%, respectively. But in similar NaCl enrichment, or control incubations, such colonies were absent. Bacterial 16S rRNA gene amplicon sequence-based alpha diversity in 50 days [Emim]Cl-enriched set was lower than the initial, control and NaCl-enriched sets (Shannon index of 6.71 vs. 8.0–8.26, respectively). Even its bacterial community structure was distinct from the remaining three sets, which clustered together. [Emim]Cl-enriched set has almost fourfold higher abundance of Proteobacteria (50.36%), with Gammaproteobacteria (32.25%) and particularly Enterobacteriaceae (24.19%) members being predominant with a predicted higher abundance of membrane transporters. Cyanobacteria , Actinobacteria and Bacteroidetes were most sensitive groups to [Emim]Cl enrichment . Although moderate halophiles can utilise their general NaCl tolerance mechanisms to resist toxicity of [Emim]Cl, abrupt exposure of the later disturbs microbial population structure and thus demands their meticulous use avoiding environmental contamination.